The Oxford handbook of postcolonial studies - Huggan, Graham, 1958- (Oxford : Oxford University Press, 2013)
This book provides a comprehensive overview of the latest scholarship in postcolonial studies, while also considering possible future developments in the field. Original chapters written by a worldwide team of contritbuors are organised into five cross-referenced sections, 'The Imperial Past', 'The Colonial Present', 'Theory and Practice', 'Across the Disciplines', and 'Across the World'. The chapters offer both country-specific and comparative approaches to current issues, offering a wide range of new and interesting perspectives. The 'Handbook' reflects the increasingly multidisciplinary nature of postcolonial studies and reiterates its continuing relevance to the study of both the colonial past - in its multiple manifestations - and the contemporary globalized world. Taken together, these essays, the dialogues they pursue, and the editorial comments that surround them constitute nothing less than a blueprint for the future of a much-contested but intellectually vibrant and politically engaged field.
Includes bibliographical references and index.
Keywords: POST COLONIALISM